2009
DOI: 10.1188/10.onf.e28-e33
|View full text |Cite
|
Sign up to set email alerts
|

Confronting the Unexpected: Temporal, Situational, and Attributive Dimensions of Distressing Symptom Experience for Breast Cancer Survivors

Abstract: Follow-up care for breast cancer survivors should foster dialogue about ways that symptoms might emerge and that unexpected situations might occur. Prospective studies are needed to examine symptom distress in terms of temporal, situational, and attributive dimensions and explore the relationship between symptom distress and psychological distress after breast cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 24 publications
4
61
1
2
Order By: Relevance
“…Previous research on cancer-related lymphoedema has tended to focus on medical help-seeking behaviours (Carter, 1997;Johansson et al, 2003;Lee et al, 2009;Rosedale & Fu, 2010;Williams, Moffatt, & Franks, 2004). Little is known about how BC patients with lymphoedema seek help from lay people to help to alleviate their challenges in everyday living.…”
Section: Introductionmentioning
confidence: 97%
“…Previous research on cancer-related lymphoedema has tended to focus on medical help-seeking behaviours (Carter, 1997;Johansson et al, 2003;Lee et al, 2009;Rosedale & Fu, 2010;Williams, Moffatt, & Franks, 2004). Little is known about how BC patients with lymphoedema seek help from lay people to help to alleviate their challenges in everyday living.…”
Section: Introductionmentioning
confidence: 97%
“…This number will expand to 3.4 million in 2015, indicating an increase of 31% [10]. Millions more people worldwide are probably grossly underestimated because of the poor or inefficient reporting systems and the lack of reliable cancer registries in third-world countries [11] [12]. Substantial advances have been made in the treatment of breast cancer, but the affordance to introduce of these methods to predict cancer at elevated risk level and to prevent this disease is still less successful [13].…”
Section: Introductionmentioning
confidence: 99%
“…The research team concluded that there were issues with the extent to which survivors in the United States and in South Africa were prepared for the possibility of lymphedema. Other researchers have found similar concerns in U.S. and Japanese survivors using qualitative and secondary analyses (Ahmed, Prizment, Lazovich, Schmitz, & Folsom, 2008;Ridner, Dietrich, & Kidd, 2011;Rosedale & Fu, 2010;Tsuchiya, Horn, & Ingham, 2012). One of the strengths of Wanchai et al (2011) is the comparisons of two cultural groups.…”
Section: Discussionmentioning
confidence: 78%